A systematic review and meta-analysis on light therapy for sleep disorders in shift workers - Chenyao Zhao; Nuoyi Li; Wenqing Miao; Ying He; Yandan Lin (Scientific Reports)
Abstract Sleep disorders constitute a significant disruption for shift workers. Beyond medical interventions, phototherapy is recognized as an effective approach to significantly alleviate sleep disorders, particularly among individuals engaged in shift work. However, the effective dose and efficacy evaluation of phototherapy have not yet been determined. This study conducted a systematic review across five databases from January 1, 1990, to December 31, 2023. A total of 11 articles were selected for meta-analysis using a random-effects model. The results showed that light therapy significantly improved the total sleep time (TST) (MD = 32.54, p < 0.00001) and sleep efficiency (SE) (MD = 2.91, p = 0.007) of shift workers compared to the control group. Subgroup analysis and regression analysis implied that medium illuminance (900–6000 lx) for a long treatment duration (≥ 1 h) during night was more effective in extending total sleep time, whereas higher-illuminance and increasing dose (lx*h) of light therapy was more beneficial for SE. In summary, light therapy has a degree of efficacy in increasing the overall sleep duration and efficiency for shift workers, the findings of the current study contribute reference and evidence for dose setting and experimental design of phototherapy on shift workers’ sleep in clinical and research.